Feasibility of Submatery Documentary Film of Diversity Concepts, Types, Ecosystems Based on Nepenthes - Alexander Sardi; Syamswisna Syamswisna; Titin Titin (Universitas Wiralodra, 2021)
This research aimed to know the Nepenthes plant species in the Nanga Nyabau forest, Kapuas Hulu Regency, and determine the feasibility of documentary film media as a learning media in the Submission of the Concept of Diversity in Genes, Types, and Ecosystems. This research was conducted through two stages. First, the Nepenthes inventory in the Nanga Nyabau Indigenous Forest, Kapuas Hulu District, then continued with the making and feasibility test of documentary films as learning media. The form of this research was descriptive. Sampling used a purposive sampling technique with the explored method. The documentary media was tested for feasibility by five validators. The validators are two lecturers of Biology Education Study Program FKIP Universitas Tanjugpura, one Biology teacher in class X of SMA Negeri 1 Putussibau, one Biology teacher in class X SMA Negeri 2 Putussibau, and one teacher of Biology in class X of SMAS Karya Budi Putussibau. Based on the results, there were five types of Nepenthes plants, namely Nepenthes bicalcarata, Nepenthes mirabilis var. echinostoma, Nepenthes rafflesiana Jack., Nepenthes reinwardtiana, and Nepenthes xneglecta. The CVI value of documentary film media was one and categorized valid to be used as a learning media